Evaluation of Atazanavir and Darunavir Interactions with Lipids for Developing pH‐Responsive Anti‐HIV Drug Combination Nanoparticles. Issue 8 (19th June 2014) - Duan, Jinghua; Freeling, Jennifer P.; Koehn, Josefin; Shu, Cuiling; Ho, Rodney J. Y.
<x xml:space="preserve">Abstract</x> We evaluated two human immunodeficiency virus (HIV) protease inhibitors, atazanavir (ATV) and darunavir (DRV), for pH‐dependent solubility, lipid binding, and drug release from lipid nanoparticles (LNPs). Both ATV and DRV incorporated into LNPs composed of pegylated and non‐pegylated phospholipids with nearly 100% efficiency, but only ATV‐LNPs formed stable lipid–drug particles and exhibited pH‐dependent drug release. DRV‐LNPs were unstable and formed mixed micelles at low drug–lipid concentrations, and thus are not suitable for lipid–drug particle development. When ATV‐LNPs were prepared with ritonavir (RTV), a metabolic and cellular membrane exporter inhibitor, and tenofovir (TFV), an HIV reverse‐transcriptase inhibitor, stable, scalable, and reproducible anti‐HIV drug combination LNPs were produced. Drug incorporation efficiencies of 85.5 ± 8.2, 85.1 ± 7.1, and 6.1 ± 0.8% for ATV, RTV, and TFV, respectively, were achieved. Preliminary primate pharmacokinetic studies with these pH‐responsive anti‐HIV drug combination LNPs administered subcutaneously produced detectable plasma concentrations that lasted for 7 days for all three drugs. These anti‐HIV LNPs could be developed as a long‐acting targeted antiretroviral therapy. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:2520–2529, 2014